1995
DOI: 10.1104/pp.108.3.1049
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expression of Three Gibberellin 20-Oxidase cDNA Clones from Arabidopsis

Abstract: Using degenerate oligonucleotide primers based on a pumpkin (Cucurbita maxima) gibberellin (CA) 20-oxidase sequence, six different fragments of dioxygenase genes were amplified by polymerase chain reaction from Arabidopsis fhaliana genomic DNA. One of these was used to isolate two different full-length cDNA clones, At2301 and At2353, from shoots of the CA-deficient Arabidopsis mutant gal-2. A third, related clone, YAP169, was identified in the Database of Expressed Sequence Tags. The cDNA clones were expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
385
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(410 citation statements)
references
References 24 publications
22
385
0
3
Order By: Relevance
“…Two cDNA clones encoding GA 20-oxidases, Ls20ox1 and Ls20ox2, and two clones encoding 3␤-hydroxylases, Ls3h1 and Ls3h2, were identified. It was already clear from other species that GA 20-oxidases are encoded by a small multigene family (Phillips et al, 1995;García-Martínez et al, 1997;Lange, 1997), and our results indicated that this is also true of 3␤-hydroxylase. Recombinant proteins from Ls20ox1 and Ls20ox2 catalyzed consecutive steps in GA biosynthesis (GA 53 3 GA 44 3 GA 19 3 GA 20 ) but formed no GA 17 , despite its being detected in extracts of lettuce seeds (Toyomasu et al, 1993).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Two cDNA clones encoding GA 20-oxidases, Ls20ox1 and Ls20ox2, and two clones encoding 3␤-hydroxylases, Ls3h1 and Ls3h2, were identified. It was already clear from other species that GA 20-oxidases are encoded by a small multigene family (Phillips et al, 1995;García-Martínez et al, 1997;Lange, 1997), and our results indicated that this is also true of 3␤-hydroxylase. Recombinant proteins from Ls20ox1 and Ls20ox2 catalyzed consecutive steps in GA biosynthesis (GA 53 3 GA 44 3 GA 19 3 GA 20 ) but formed no GA 17 , despite its being detected in extracts of lettuce seeds (Toyomasu et al, 1993).…”
Section: Discussionsupporting
confidence: 68%
“…With regard to the regulation of elongation growth (described above), it has been suggested that Pfr might suppress GA biosynthesis. GA 20-oxidase transcript levels are subject to feedback regulation (Phillips et al, 1995;Martin et al, 1996;Toyomasu et al, 1997); GAdeficient mutants accumulate a high level of 20-oxidase mRNA, which is markedly reduced by application of bioactive GA. Our preliminary experiments showed that, similar to Ls20ox2, the expression of the Ls20ox1 and Ls3h1 genes, which were not negatively regulated by far-red-/ red-light treatment, was markedly decreased by treatment with GA 1 (data not shown). Furthermore, we cannot yet say whether the endogenous GA 1 generated within 3 h of incubation after a far-red-/red-light treatment is sufficient for negative feedback regulation to achieve the observed decrease in the Ls20ox2 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26). There are many reports on the expression of recombinant enzymes retaining catalytic activity as fusion proteins (7)(8)(9)(10)(11)(12)(13)(14)(15)(26)(27)(28)(29). Therefore, the method described here should be applicable for cloning a wide range of enzymes, provided that these are not involved in the metabolism of or are toxic to E. coli itself.…”
Section: Discussionmentioning
confidence: 99%
“…First, the oxidation at C-7 converts the aldehyde to the carboxylic acid to give GA 12 . Then, sequential oxidation at C-20 eventually produces two kinds of products: a tricarboxylic acid (GA 25 ) or, with loss of C-20 and lactonization, a C 19 -GA (GA 9 ). 3␤-Hydroxylation produces a parallel series leading to the corresponding C-20 carboxylic acid (GA 13 ) and C 19 -lactone (GA 4 ).…”
mentioning
confidence: 99%